Pendidikan Islam dan Tantangan Kontemporer: Strategi Mengatasi Radikalisme dan Ekstremisme Melalui Pendidikan Holistik - Amie Primarni, Amie Primarni (Jurnal Dirosah Islamiyah, 2024)
This article discusses the role of Islamic education in facing contemporary challenges, especially in addressing the problems of radicalism and extremism. Through an interdisciplinary approach, this article investigates how Islamic education can serve as an effective solution in responding to the phenomenon. In this article, we will analyze the main concepts in Islamic education that promote a correct understanding of religion, tolerance, moderatism, and criticism of extreme thought. Through proper education, the values of tolerance, justice, and moderation can be instilled in the younger generation of Muslims. This article highlights the concept of inclusive Islamic education, based on balanced religious teachings, and developing critical understanding. This research was conducted through literature review and contextual analysis to provide deeper insight into the importance of Islamic education in addressing contemporary challenges. The results show that holistic and contextual Islamic education can play an important role in preventing and overcoming radicalism and extremism. This article provides a new outlook for educators, education practitioners, and policy makers to promote well-rounded Islamic education and build a generation of civilized Muslims.